EFFECTIVENESS OF TACTICS FOR SELECTING ARTIFICIAL CROWNS IN PATIENTS WITH ALLERGIC BACKGROUND - Khojimurodov Jamshidbek Eraliyevich (TADQIQOTLAR, 2026)
Abstract.  According  to  official  statistics  in  Uzbekistan,  10–15%  of  the population (depending on the region) suffers from allergic diseases. Studies on the incidence and prevalence of allergic diseases in different countries indicate that these conditions currently affect 20–40% of the population.